Sodium Silicate Gel Effect on Cemented Tailing Backfill That Contains Lead-Zinc Smelting Slag at Early Ages. (24th January 2018) - Guo, Lijie; Li, Wenchen; Yang, Xiaocong; Xu, Wenyuan
Abstract : This paper presents the results of an experimental study on the priming effect of sodium silicate gel (SS) on cemented tailing backfill (CTB) that contains lead-zinc smelting slag. CTB and cemented paste (CP) containing lead-zinc smelting slag samples with SS of 0 and 0.4% of the mass of the slag were prepared and cured at 20°C for 1, 3, 7, and 28 days. Mechanical test and pore structure analyses were performed on the studied CTB samples, microstructural analyses (X-ray diffraction analysis and thermal gravity analysis) were performed on the studied CP samples, whereas the electrical conductivity of CTB was monitored. The results reveal that SS has a significant positive effect on cementitious activity of binder mixed by cement and lead-zinc smelting slag. This activation leads to the acceleration of binder hydration process, the formation of more cement hydration products in the CTBs, and the refinement of their pore structure, which is favorable for the strength development of CTB.